The relationship between stringent nutrients policies and innovations in the wastewater sector - Rostedt, Johan (SLU/Dept. of Economics, 2014)
A first step in the so-called Porter hypothesis relates to the link between stringent environmental policy and increased innovativeness. This thesis tests this step by investigates the relationship between stringent policy on phosphorus and nitrogen emissions in Sweden and the number of innovations that aim to reduce these emissions. Regulations and laws, introduced during the period 1960 – 2010, are used in order to measure the stringency of the policy. Patent data is used to reflect the number of innovations during the period in question. Three models, based on different sub periods, capture an eventual relationship from an econometric analysis. The result from the econometric analysis suggests that a relationship exist in the case of phosphorus, but not in the case of nitrogen. The model that takes into account the periods in which the targets from the regulations and laws were reached captures the expected development best.